OUTCOMES OF PRENATAL INTERVENTION FOR MONOCHORIONIC DIAMNIOTIC TWIN PREGNANCIES COMPLICATED BY TWIN REVERSED ARTERIAL PERFUSION (TRAP) SEQUENCE IN HA NOI OBSTETRICS AND GYNECOLOGY HOSPITAL (Tạp chí Y học Cộng đồng, 2026)
Objective: To evaluate of prenatal management outcomes in monochorionic diamniotic twin pregnancies complicated by twin reversed arterial perfusion (TRAP) sequence in Ha Noi Obstetrics and Gynecology Hospital.Material and Methods: An interventional study combined with longitudinal follow-up was conducted on 15 patients with acardiac twin in TRAP sequence who underwent selective umbilical cord laser photocoagulation, delivered at Hanoi Obstetrics and Gynecology Hospital, and whose neonates were followed for at least six months postpartum from January 2020 to December 2021.Results: The mean gestational age at intervention was 19.05 ± 3.36 weeks, and the mean operative time was 40.1 ± 9.0 minutes. The intraoperative complication rate was 0%; there were no complications within 24 hours postoperatively, and 26.67% of cases developed complications within 7 days after surgery.Conclusion: The average gestational age at intervention was approximately 19 weeks, with an average operative time of 40 minutes. The intraoperative complication rate was low.
Keywords: Twin reversed arterial perfusion (TRAP) sequence, management of TRAP sequence, surgical treatment of TRAP sequence